The Impact of Ethical Leadership on Employees’ Green Innovation Behavior: A Mediating-Moderating Model - Yang, Liqin; Liu, Haibing (Frontiers in Psychology, 2022)
To enhance environmental protection and sustainable development, green innovation (GI) is an inevitable choice for enterprises. This study incorporates social identity theory and social learning theory to explore the impact of ethical leadership on employee GI behavior. In addition, this study also examines the mediating effects of green organizational identity (GOI) and the moderating role of strategic flexibility (SF). Using structural equation modeling, an empirical survey was conducted among 300 Chinese manufacturing companies. The study found that ethical leadership (EL) positively affects employees’ green innovation behavior (EGIB). It also positively impacts the GOI, which led to EGIB. In addition, the study also confirmed that GOI played a mediating role in the relationship between EL and EGIB. The results further indicated that SF positively enhanced the effect of GOI on EGIB. The findings have important contributions to theory and practice in the current research context.